Oregon Youth Study Wave 2, 1984-1986 - Capaldi, Deborah M. ([Verlag nicht ermittelbar], 2021)
The original Oregon Youth Study began 1983. The goal was to examine the etiology of antisocial behaviors in boys, with a view to designing preventive interventions within the context of the family and the school. This longitudinal study has expanded over the past few decades into an intergenerational study, retaining the original young men and including their partners and children. Demographic variables include race, religion, annual household income, and the participants' parents' employment statuses.